AN IN SILICO ANALYSIS OF GINGER EXPRESSED SEQUENCE TAGS FOR MICROSATELLITES - Ince, A. G.; Karaca, M.; Onus, A. N. (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
Ginger (Zingiber officinale Roscoe) is a perennial plant in the family Zingiberaceae and rhizomes of ginger have been used in folk medicine and cooking. However, ginger production is seriously affected by several diseases. DNA based technologies can be applied for the identification of wild germplasm or commercially important plants with fungal and bacterial resistance genes. There exists limited research on the characterization of ginger germplasm. Microsatellite or simple sequence repeat (SSR) is very powerful marker for germplasm identification and plant genetic mapping studies. In this paper we used a total of 138,139 expressed sequence tags (ESTs) constructed from tissues representing various tissue types (leaves, roots, rhizomes) to identify new microsatellite primer pairs and investigate the distribution and frequency of microsatellites in Zingiber officinale Roscoe ESTs obtained from leaf, root and rhizome libraries. Based on the obtained results we concluded that different tissues of Zingiber officinale Roscoe ESTs possessed different amounts of microsatellites and microsatellite compositions indicating the distribution of microsatellites among the tissues or organs was not random differing from plant and animal repeats found in genomic microsatellites. Microsatellite compositions of the root ESTs were quite different from those leaf and rhizomes. In this study we also designed several dozens microsatellite primer pairs which could be used to detect the marker-QTL or comparative mapping and homologous gene cloning for ginger breeding studies. Publicly available Zingiber officinale Roscoe ESTs are valuable for in silico gene expression studies including for the development of microsatellite and single nucleotide polymorphism (SNP) PCR-based molecular markers.